Neon signage as cultural placemakers in America - Leda Cempellin (Interdisciplinary Journal of Signage and Wayfinding, 2024)
This exploratory qualitative case study examines the cultural significance of Carlos and Ed Garcia’s neon sign collection as components of American cultural heritage. By integrating secondary sources from human geography, cultural history, and philosophy, along with conversation with Carlos Garcia and photographic documentation primarily from the Garcia collection, this study analyzes how neon signs in American landscapes embody the interplay between mobility and permanence. These signs transition from functional advertisements to nostalgic artifacts, sparking reflections on the tension between historical restoration and artistic revitalization. The presence of these grandfathered and orphan signs in situ, long after the associated businesses have closed, stands as the last nostalgic remnant resisting a sense of placelessness, where unique local identities are overshadowed by corporate landscapes. Removal of these signs from their original locations and reorganization within a private museum underscores the tension between original and reimagined contexts. The findings provide a deeper understanding of the cultural narratives embedded in neon signage from this collection, emphasizing their unique value in American cultural heritage and their evolving role in expressing and interpreting communal and cultural identities.